Agrobacterium-Mediated Transformation of Javanica Rice Plants With A Cry1b Gene Under The Control of Wound-Inducible Gene Promoter - Estiati, Amy; Rahmawati, Syamsidah; Astuti, Dwi; Loedin, Inez H.S (ANNALES BOGORIENSES, 2007)
A  cry1B synthetic gene of Bacillus thuringiensis has been used  for  the transformation of the javanica rice plants  cv.  Rojolele  confer resistance  to  an  important  pest,  yellow  stem  borer  (Scirpophaga  incertulas). Embryogenic callus were co-cultivated with  the EHA 105 strain of Agrobacterium tumefaciens harbouring binary vector CAMB  IA 130 I containing cry  / B gene under  the control of wound inducible gene promoter  (mpi), hygromycin resistance gene (hpt)  as a selectable marker and intron-containing β-glucuronidase (gus - intron) gene al) a reporter gene  driven  by  CaMV35S  promoter.  Previously.  our  histochemical  assay  and  P  R  analyses.  had  proved  th integration of  cry1B gene  into  the genome of rice plants at first generation .  However,  the existence of the gene should remain  table  throughout generation.  In  this study,  the presence of the cry1B transgene in  rice  transgenic plants at  second generation was confirmed by Polymerase Chain Reaction (PCR) .  Insertion of  the cry1B gene in the genome of PCR positive plants was  verified by Southern blot analysis is and showed that integration of cry1  B  into the genomic DNA of  javanica rice plants cv. Rojolele.  An effective resistance of transgenic  plants against  stem borer was verified in  bioassays.